A prospective study on pulse wave velocity (PWV) and response to anti-hypertensive treatments: PWV determines BP control. (15th January 2015) - Zheng, Meili; Huo, Yong; Wang, Xiaobin; Xu, Xin; Qin, Xianhui; Tang, Genfu; Xing, Houxun; Fan, Fangfang; Li, Jianping; Zhang, Yan; Wang, Binyan; Xu, Xiping; et al.
Abstract: Objectives: Recent data indicate that hypertension is not well controlled in many populations throughout the world. The factors that influence individual response to anti-hypertensive treatment need to be clarified. Pulse wave velocity (PWV), as a marker of arterial stiffness, has been demonstrated to have important relationships with BP progression; however, little information is available on the role of PWV in blood pressure (BP) control. We aimed to assess BP control during the run-in treatment period in the China Stroke Primary Prevention Trial (CSPPT). Methods and results: These analyses included a total of 3056 treated hypertensive subjects (age: 59.6 ± 7.5 years, male/female 1339/1717) with PWV measured at baseline. The average BP at enrollment was 166/95 mm Hg, and declined to 141/85 mm Hg after short-term antihypertensive treatment (a median follow-up of 20 days). There was an inverse relationship between PWV level and BP reduction during the treatment, most notably for systolic BP (with estimated coefficients of − 9.01 (P < 0.001) for the top quartile, as compared to the bottom quartile). The association did not differ significantly by gender or types of antihypertensive drugs. Factors related to smaller BP decline were low baseline BP, high baseline PWV, high body mass index, high creatinine, use of fewer types of antihypertensive drug, high heart rate (only for SBP), high homocysteine and low age (only for DBP). Conclusion: PWV appears to be an independent determinant of individual response to anti-hypertensive treatment. Highlights: Baseline PWV predicts SBP response to drug treatment in a dose-response manner. The impact of baseline PWV on SBP control was not affected by other variables. Baseline PWV also affects DBP control; however, the impact is smaller. Factors influencing SBP and DBP controls are proven to be different.